Determination of optimum sodium bicarbonate injection rates for acid hydrochloric scrubbing in a clinical waste incineration plant - Suleiman, Mohd. Salleh (2012)
Clinical wastes are heterogeneous in nature and fluctuations in the waste components have a direct effect on the sorbent capture rates. This research was conducted to determine the optimum sodium bicarbonate (NaHCO3) injection rates for acid hydrochloric (HCl) scrubbing in a clinical waste incineration plant. The plant employs a rotary kiln system having burning capacity of 300 kg/h of clinical waste and operated on a 24 h/day basis. Currently the plant meets all the emission parameters set by the Department of Environment (DOE) even at excessive injection rates of NaHCO3. The NaHCO3 injection rate is 25 kg/h, which was recommended by plant manufacturer to meet maximum standard emission limit of 100 mg/Nm3 HCl. Moisture content (relative humidity) and stoichiometric ratio of adsorbent and acid mist were the main parameters influencing the acid gases removal. To overcome the excessive injection of NaHCO3, analysis of HCl emission at various injection rates of 25, 20, 15 and 10 kg/h were conducted. The results on HCl emission after injection of NaHCO3 were in the range of 0.58-7.13, 5.63-7.74, 0.07- 2.99 and 3-28 mg/Nm3, respectively. The results showed that NaHCO3 injection rate as low as 10 kg/h could still meet the HCl stipulated emission limit. It can be concluded from this study that an optimum injection rate would not only save cost and reduce wastage but also reduce bag house loading rate and prolong the life span of filter bags. A further study was conducted for chlorine (Cl2) and HCl emissions at the point of before and after the injection point of NaHCO3, showed inverse proportional relationship between both parameters. Total Cl2 concentration was lower at the point of after injection point of NaHCO3, lower temperature was observed with higher water vapor (H2O) present had reduced the amount of Cl2 present. The reduction in emission concentration ranges from 56% to 97% after NaHCO3 injection at a slight reduced temperature. Most of the chlorine atom will leave the incinerator as HCl, but a considerable part is in the form of Cl2.